Innovation and Marketing in the Video Game Industry : Avoiding the Performance Trap - Wesley, David T. A. (Gower, 2010)
"Video games have had a greater impact on our society than almost any other leisure activity. They not only consume a large portion of our free time, they influence cultural trends, drive microprocessor development, and help train pilots and soldiers. Now, with the Nintendo Wii and DS, they are helping people stay fit, facilitating rehabilitation, and creating new learning opportunities. Innovation has played a major role in the long term success of the video game industry, as software developers and hardware engineers attempt to design products that meet the needs of ever widening segments of the population. At the same time, companies with the most advanced products are often proving to be less successful than their competitors. Innovation and Marketing in the Video Game Industry identifies patterns that will help engineers, developers, and marketing executives to formulate better business strategies and successfully bring new products to market. Readers will also discover how some video game companies are challenging normal industry rules by using radical innovations to attract new customers. Finally, this revealing book sheds light on why some innovations have attracted legions of followers among populations that have never before been viewed as gamers, including parents and senior citizens and how video games have come to be used in a variety of socially beneficial ways. David Wesley and Gloria Barczak's comparison of product features, marketing strategies, and the supply chain will appeal to marketing professionals, business managers, and product design engineers in technology intensive industries, to government officials who are under increasing pressure to understand and regulate video games, and to anyone who wants to understand the inner workings of one of the most important industries to emerge in modern times. In addition, as video games become an ever more pervasive aspect of media entertainment, managers from companies of all stripes need to understand video gaming as a way to reach potential customers"--Provided by publisher.